The Role of Podcast as a Distance Learning Media during Covid-19 in Higher Education - Anindhita, Wiratri; Nugrahaeni, Elisabeth; Rahmawati, Devie; Viendyasari, Mila (AIBPM Publisher, 2022)
The Covid-19 pandemic that hit the world has changed human life in all areas of life, including education. In education, learning and instruction are important to higher education students. Covid-19 affected learning design from face-to-face learning in the class become distance learning. Distance learning is an institution-based formal education in which students and instructors are located in separate locations, thus requiring an interactive telecommunication system to connect the two and the various resources required in it. Many things need to be fixed and updated in terms of materials and platforms used. This study uses a descriptive qualitative method to show the need for distance learning innovation by using podcast media as an additional alternative platform to answer distance learning challenges. The results showed that the podcast system in the form of recordings made it easier for students to listen to the material presented by the instructor. Podcasts made students enthusiastic about learning during the Covid-19 pandemic.